Influence of amphotericin B on liquid crystal state of the Cholesterol/Dipalmitoylphosphatidylcholine monolayer in the presence of different metal cations - 王娟 史瑞新 孙润广 郝长春 李俊花 逯晓龙 (Chinese physics B, 2016)
Amphotericin B is a very effective antifungal drug,but it has an adverse reaction to the membrane of mammals＇ cells.The interaction between Am B and cholesterol（Chol） causes the formation of pores on the membrane to destroy its integrity.In particular,Am B has a significant effect on the permeability of membrane for K~＋ions.It has been reported that Na＋ions and Ca~（2＋）ions may have some influence on the interaction between amphotericin B and lipid molecules.In this work,the effects of these metal cations on the physical state and intermolecular interaction of the Cholesterol/Dipalmitoylphosphatidylcholine（Chol/DPPC） monolayer with and without Am B have been investigated.The addition of Am B induces the change of physical state of the lipid monolayer from liquid-gel phase to liquid phase.Different metal cations could influence the phase transition of the Am B-lipid monolayer.The K~＋ions and Ca2＋ions make the obvious phase transition disappear.However,the presence of Na＋ions has little influence on the phase transition of the Am B-lipid monolayer.The addition of Am B and the presence of different metal cations weaken the attractive force on the monolayers.After addition of Am B,the force between the molecules is the strongest in the environment of K＋ions,thus is the weakest in the environment of Ca~（2＋）ions,which may be due to the distribution of these metal cations inside and outside of cells.A large number of K＋ions distribute inside of the cells,thus most of Na＋and Ca~（2＋）ions exist out of the cells.Hence,it may be possible that when Am B molecules are out of the cells,the reaction between the drug and lipid molecules is weaker than that inside the cells.These results may have a great reference value for further studying the toxicity mechanism of Am B and the influence of metal cations on the membrane.